Treatment of post-intubation laryngeal granulomas: systematic review and proportional meta-analysis - Rimoli, Caroline Fernandes [UNESP]; Martins, Regina Helena Garcia [UNESP]; Catâneo, Daniele Cristina [UNESP]; Imamura, Rui; Catâneo, Antonio José Maria [UNESP] (Elsevier, 2018)
Introduction: Laryngeal granulomas post intubation are benign but recurrent lesions. There is no consensus for its treatment. Objective: To describe the effectiveness of different treatment modalities for primary or recurrent laryngeal granulomas resulting from endotracheal intubation. Methods: Systematic review and proportional meta-analysis. Eligibility criteria – experimental or observational studies with at least five subjects. Outcomes studied – granuloma resolution, recurrence, and time for resolution. Databases used – Pubmed, Embase, Lilacs, and Cochrane. The Stats Direct 3.0.121 program was used. Results: Six studies were selected, with 85 patients. The treatments registered were: antireflux therapy, speech therapy, anti-inflammatory drugs, steroids, antibiotics, zinc sulfate and surgery. 85 patients from six studies had primary treatment: surgery ± associations (41 patients), resolution chance 75% (95% CI: 0.3–100%, I2 = 90%), absolute relapse risk 25% (95% CI: 0.2–71%); medical treatment (44 patients), resolution chance 86% (95% CI: 67–97%); and absolute relapse risk 14% (95% CI: 3–33%). There was no significant difference between groups. Three studies, encompassing 19 patients, analyzed secondary treatment (failure or recurrence after primary treatment); three subjects presented new recurrence. The time needed to resolve the lesions varied from immediate, after surgery, to 23 months, for inhaled steroid. Conclusion: There is no evidence of high quality that proves the efficacy of any treatment for laryngeal granulomas resulting from endotracheal intubation.
Tratamento de granulomas laríngeos pós-intubação: revisão sistemática e meta-análise proporcional
Keywords: Granulomas; Larynx; Systematic review; Treatment